Understanding TikTok’s Influence on EFL Students’ Script-Writing Development through Qualitative Research - Dwi Saputra, Ade; Ferdiyanto, Feri; Islam, Raudhatul (Fakultas Sastra - Universitas Muslim Indonesia, 2025)
This qualitative study explores the influence of TikTok on the English script-writing development of Indonesian EFL students in a pesantren-based language learning program. Using a case study design, six students and one instructor participated through interviews, classroom observations, questionnaires, and analysis of student-generated scripts. The study aimed to identify how sustained exposure to TikTok's short-form, multimodal content shapes learners’ written expression, creativity, and linguistic awareness. Findings reveal that TikTok fosters increased expressiveness, narrative concision, and audience sensitivity in student scripts. Participants drew from platform features such as trending language, dialogic cues, and visual storytelling, which they translated into idiomatic phrases, informal transitions, and creative dialogue structures in writing. The social and interactive nature of TikTok encouraged risk-taking and self-regulated learning behaviors, including rewatching videos for tone and accuracy and mimicking fluent speech. However, the study also highlights persistent challenges, particularly in grammar accuracy and register appropriateness, suggesting that while TikTok can stimulate creativity and engagement, it does not inherently provide corrective feedback or support formal writing norms. Educators are encouraged to incorporate TikTok thoughtfully using it as a scaffold for idea generation and stylistic awareness while complementing it with explicit instruction in grammar and genre conventions. This research contributes to evolving perspectives on the integration of social media in second language writing pedagogy.